2015
DOI: 10.1111/jsr.12296
|View full text |Cite
|
Sign up to set email alerts
|

Are qualitative and quantitative sleep problems associated with delinquency when controlling for psychopathic features and parental supervision?

Abstract: SUMMARYThe aim of this study was to explore the relationship between sleep, including both qualitative and quantitative aspects, and delinquent behaviour while controlling for psychopathic features of adolescents and parental supervision at bedtime. We analysed data from a nationally representative sample of 4855 Finnish adolescents (mean age 15.3 years, 51% females). Sleep problems, hours of sleep and delinquency were evaluated via self-report. Psychopathic features were measured with the Antisocial Process S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
2
17
0
1
Order By: Relevance
“…Although we did not begin this work with explicit predictions about age, the main effect of age on overnight consolidation is not unexpected given observed differences in sleep habits between adolescents (e.g., high school students who often get too little sleep) and adults (see Carskadon, 2011). As such, this finding adds to a growing literature that highlights the importance of overnight consolidation (including sleep) for learning and academic achievement in adolescents (e.g., Backman et al, 2015; Bartel et al, 2016). Further research on the relationship between word learning and overnight consolidation that includes measures of sleep duration and quality in this age range would help elucidate this relationship.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although we did not begin this work with explicit predictions about age, the main effect of age on overnight consolidation is not unexpected given observed differences in sleep habits between adolescents (e.g., high school students who often get too little sleep) and adults (see Carskadon, 2011). As such, this finding adds to a growing literature that highlights the importance of overnight consolidation (including sleep) for learning and academic achievement in adolescents (e.g., Backman et al, 2015; Bartel et al, 2016). Further research on the relationship between word learning and overnight consolidation that includes measures of sleep duration and quality in this age range would help elucidate this relationship.…”
Section: Discussionsupporting
confidence: 60%
“…Specifically, our findings suggest that there are age-related changes in the relationship between sleep and cortical consolidation, which continue into late adolescence. These age-related changes may be driven by differences in the amount of sleep or quality of sleep between younger and older adolescents, which have previously been studied in the context of adolescent mental health status and academic achievement (e.g., Backman et al, 2015; Bartel et al, 2016). Critically, our finding of reduced cortical consolidation in the posterior cingulate/precuneus for poorer readers and those with lower vocabulary scores implicates overnight cortical consolidation as one possible factor in reading and language disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is critical for adolescents' daily functioning [1,2]. With longer sleep duration, adolescents have improved capabilities to learn, remember and perform well academically [3,4], and decreased rates of motor vehicle accidents [5], whereas less than seven hours of sleep per night is associated with higher rates of delinquency and crime [6]. Poorer mental health is associated with adolescents who obtain less than seven hours sleep per night, compared to adolescents who sleep seven to nine hours per night [7].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the quantitative sleep analysis, the results demonstrated that there was no clear difference among the subjects. The difference between these qualitative and quantitative sleep analysis results in evaluating the sleep quality has been reported several times in the other studies [118][119][120][121][122]. Considering the environment of this experiment might be unfamiliar to the participants even though the first night sleep effect [54] was considered and that the sleep duration of the participants was limited during the experiment, the subjective feedback from the participants in a qualitative level might have been affected.…”
Section: Discussionmentioning
confidence: 82%